The Effect Of Teaching Mathematics Using The Exploratory Learning Strategy On The Achievement Of Fourth-Grade Primary School Students (Journal of the College of Basic Education, 2025)
The aim of the research is to identify the effect of using the Exploratory Learning strategy on the achievement of fourth-grade primary school students.The research sample was randomly selected from Salman Al-Muhammadi Primary School for Boys affiliated to the General Directorate of Education of Dhi Qar, Al-Nasr Education Department, and consisted of (48) students from the fourth grade of primary school, with (24) students in each group of the experimental and control research groups. The two groups were rewarded in the following variables (chronological age in months, previous mathematical knowledge, previous achievement, intelligence, and the educational level of the parents), and the experimental class in the second semester of the academic year (2024-2025) AD. The research tool was prepared, which is an achievement test in mathematics consisting of (15) objective paragraphs of the multiple-choice type, using the Kuder-Richardson equation (K20) The value of the reliability coefficient was (0.73). The research tool was applied at the end of the experiment, and after collecting the data and using appropriate statistical methods, the results showed that the students of the experimental group who studied using the Exploratory Learning strategy were superior to the students of the control group who studied using the traditional method. In light of the results, a number of recommendations and proposals were made.